Letter (copy) : Basque Children - Tewson, Vincent
1946-10-02 038-0013-002 Secretary's. HVT/EK/1192. 2nd October, 1946. Mr. Ronald Thackrah, 5, St. Mary's Avenue, London, N.3. Dear Ronald, Basque Children. The enclosed is correspondence which I have received from Mr. David Grenfell, M.P. I am passing the matter to you in the hope that you may be able to arrange for the case to be dealt with direct. I hope you are keeping fit. Yours sincerely, Acting General Secretary. Original correspondence. 292/946/38/13(II)